Preferences for Using an Integrated eCampus to Support Learning in Higher Education - Mahmudi, Mahmudi; Said Hasibuan, M.; Lestari, Sri (COUNS-EDU: The International Journal of Counseling and Education, 2025)
This study adopts the Technology Acceptance Model (TAM) as a theoretical framework to analyze the influence of system factors and organizational structure on the successful implementation of integrated eCampus systems in higher education. Digital transformation in higher education is a complex challenge influenced by system quality, information quality, organizational support, managerial support, and human resource capacity.The research uses a quantitative approach, with data collected through surveys and analyzed using PLS-SEM. The results confirm that the measurement model exhibits adequate validity and reliability. The inner model analysis reveals that all hypothesized relationships between constructs are statistically significant.Crucially, the paths demonstrating the greatest influence were the relationship of Perceived Ease of Use to Perceived Usefulness (? = 0.735) and Behavioral Intention to Use to User Satisfaction (? = 0.727).These findings confirm that perceived ease of use and behavioral intention to use are key factors in increasing perceived benefits and user satisfaction with the eCampus system. This research offers theoretical contributions to the development of the TAM model and practical implications for policymakers in designing effective and sustainable academic information system implementation strategies.